2011
DOI: 10.1152/ajprenal.00661.2010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the protein kinase MK-2 protects podocytes from nephrotic syndrome-related injury

Abstract: While mitogen-activated protein kinase (MAPK) activation has been implicated in the pathogenesis of various glomerular diseases, including nephrotic syndrome (NS), its specific role in podocyte injury is not known. We hypothesized that MK-2, a downstream substrate of p38 MAPK, mediates the adverse effects of this pathway and that inhibition of MK-2 would protect podocytes from NS-related injury. Using cultured podocytes, we analyzed 1) the roles of MK-2 and p38 MAPK in puromycin aminonucleoside (PAN)-induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 70 publications
2
27
1
Order By: Relevance
“…Inhibition of p38 MAPK and possibly ERK1/2 in PAN and doxorubicin animal models of NS has been reported to suppress proteinuria and actin reorganization in podocytes (Koshikawa et al, 2005). In addition, we have shown that inhibiting either p38 MAPK or its downstream substrate MK2 prevents PAN-induced injury to podocytes (Pengal et al, 2011). Increased amounts of activated ERK and p38 MAPK 9.…”
Section: Discussionmentioning
confidence: 69%
“…Inhibition of p38 MAPK and possibly ERK1/2 in PAN and doxorubicin animal models of NS has been reported to suppress proteinuria and actin reorganization in podocytes (Koshikawa et al, 2005). In addition, we have shown that inhibiting either p38 MAPK or its downstream substrate MK2 prevents PAN-induced injury to podocytes (Pengal et al, 2011). Increased amounts of activated ERK and p38 MAPK 9.…”
Section: Discussionmentioning
confidence: 69%
“…In animal experimental models of glomerulopathies, activation of p38 MAPK or JNK is necessary for podocyte injury and proteinuria (40,43). Consistently, inhibition of these SAPKs prevents podocyte injury, suppresses proteinuria in animal models, and mitigates glomerulonephritis (41,(43)(44)(45)(46). Importantly, HIV-1 GP120-induced tubular epithelial apoptosis is also mediated by p38 MAPK signaling (47).…”
Section: Apol1 Risk Variants Hyperactivate Sapks Known To Mediate Kidneymentioning
confidence: 89%
“…The same compound also improved cell viability in a nephrotic syndrome-related podocyte injury model by inhibition of MK2 activity and consequent reduction of COX-2 mRNA expression and Hsp27 phosphorylation. 48 On the other hand, 7 was used as MK2 inhibitor to study how senescence underwent an acceleration in fibroblasts from human WS, without reaching conclusive and unambiguous results. 49 …”
Section: Crystallization Studiesmentioning
confidence: 99%